A Transtheoretical Model in Controlling Smoking Behavior in Junior High School Students in Palu City, Indonesia: A Systematic Review - Muhammad Ryman Napirah1,2, Ridwan Amiruddin3, Sukri Palutturi4, Stang5, Aminuddin Syam6, Rosmala Nur (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: The average child first tries and is accustomed to smoking when sitting in seventh and eighthgrade junior high school (SMP) or around the age of 12-13 years. In TTM Model (Transtheoretical Model),there are 5 stages of TTM. The purpose of this systematic review is to develop a model of transtheoretical incontrolling smoking behavior in junior high school students in Palu City, Indonesia.Method: This research used a systematic literature review. Various references were collected from onlinedatabase including reports, journals, and books in the last 10 years. The journals were mostly from thescholarly journals. The articles were screened according to the research objectives. The keywords used aretranstheoretical model and smoking behavior in junior high school students.Results: This study showed that the use of a transtheoretical model is very effective in controllingsmoking behavior in junior high school students. There are 5 stages of TTM, namely pre-contemplation(contemplation to stop smoking), contemplation (contemplation to stop smoking in the next 6 months),preparation (contemplation to stop smoking in the next 30 days), action (already stopped smoking in 6months), and maintenance.Conclusions: This paper concludes that a model using transtheoretical is effective for control smokingbehavior in junior high school students. Further recommendation will be provided.